Implikasi Keruangan Pemindahan Pelabuhan Jayapura ke Pelabuhan Depapre - Rayhatson, Lukman Enrico; Ma'rif, Samsul (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
Jayapura port currently functions for the transportation of both passengers and cargo for Jayapura city and its hinderland. Movement of ships and goods continue to increase along with economic growth of the area resulting in inadequate area for container storage. This had become the basis for Papua Province Government to separate the function of cargo port from Jayapura to Depapre district. This study aims to investigate the spatial implication of the movement of the port. The study identifies the role and function of Jayapura and Depapre Port, the burden and benefit of the movement of the port for Jayapura and Depapre, and its spatial implication. The study employs descriptive quantitative approach using analytic hierarchy process (AHP). Analyses showed that Jayapura Port functions mainly to serve exports and supply of consumer goods, while Depapre will provide complementary functions in the early stages while demand for cargo grows from nearby production centers. The burden faced by Jayapura is the increase in distribution cost, along with environmental degradation in Depapre. The benefits include more efficient distribution process in Jayapura and economic development in Depapre. The spatial implications include a shift of land use in the surrounding of Depapre and along the Sentani-Depapre corridor. These shifts will require land use controlling measures in Depapre and along the Sentani-Depapre corridor.